APPLICATION OF CONDITIONAL PROBABILITY IN PREDICTING INTERVAL PROBABILITY OF DATA QUERYING - Intan, Rolly (Jurnal Informatika, 2004)
This paper discusses fuzzification of crisp domain into fuzzy classes providing fuzzy domain. Relationship between two fuzzy domains, Xi and Xj, can be represented by using a matrix, wij. If Xi has n elements of fuzzy data and Xj has m elements of fuzzy data then wij is n x m matrix. Our primary goal in this paper is to generate some formulas for predicting interval probability in the relation to data querying, i.e., given John is 30 years old and he has MS degree, how about his probability to get high salary.